EXISTENTIAL HUMAN NEEDS IN PAULO COELHO’S ELEVEN MINUTES - Pioro B. Simarmata; Erwin Simanullang (Muse: Jurnal of Art, 2023)
This study deals with the existential human needs in Paulo Coelho’s Eleven Minutes. The novel is seen as a representation of people who agree that love, money and sex are among the existential human needs. This is a library research and applies the mimetic theory proposed by M. H. Abrams that states literature as an imitation of the real life. The analysis focuses on how characters trying to look for love, money, and sex which is shown through the character Maria. She tries to pursue those three needs. At first, she tried to find love although it ended in failure and resulted in her not believing in love. At first maria tried to earn money for her family, but she’s starting to earn it for herself and starting to save up for her dream to travel to Geneva, Switzerland. In Switzerland, she works as a salsa dancer where unfortunately things don’t work out for her and she needs to obtain a lot of money in order to return to her home country. After a series of events, Maria decided to sell her body as an escort since she finds that it is easier to obtain money that way. She later meets with Ralf and fall in love with him however she later finds out that Ralf is involved in the escort business. This young and handsome painter, Ralf, taught her many things in life and also one of the main reasons that made her wanting to become a better person. In her experiences, Maria was able to fulfil those three needs: love, money and sex. In conclusion, Paul Coelho's, in his novel, describes the existential human needs which are: love, money, and sex to continue life.